Bacillus calmette–Guérin scar inflammation after COVID vaccination - B N Shiva Prasad (Indian Journal of Rheumatology)
Bacillus Calmette–Guérin (BCG) scar inflammatory reactions have been commonly reported with Kawasaki disease in children and less commonly with other viral infections. Postvaccination BCG scar inflammation has only been reported with the influenza vaccine. Two cases of post-COVID vaccination BCG scar inflammation has been recently reported. we report a case of BCG scar inflammation appeared after 24 h of vaccination of both the doses of vaccine.